Progress in Cobalt Complexes for Enabling Asymmetric Hydrogenation, H2 Production Catalysis and Alkene/Alkyne Hydro‐functionalization: A Review - Kumari, Shalima; Thakur, Maridula; Kumari, Meena (ChemistrySelect (Weinheim), 2024)
The use of hydrogen as an alternate clean fuel over conventional fuels, in addition to its role in chemical industries giving rise to useful products like hydrocarbons, has been the subject of research for many years. The need for hydrogen gas production methods has ever since been in demand. This review offers a comprehensive exploration of applications of cobalt complexes in asymmetric hydrogenation, H2 production catalysis and the hydro‐functionalization of alkenes and alkynes. Cobalt metal stands out, particularly due to its distinctive involvement in potential single‐electron processes. The main objective of this review is to provide an insight into the role of cobalt‐based coordination complexes as catalysts in hydrogenation reactions. It delves into models for enantio‐induction and extensively investigates the role of cobalt complexes in hydrogen evolution and associated reactions. Cobalt selection as the central metal is attributed to its beneficial (II)/(III) redox couple state, which proves valuable in hydride transfer reactions. While the review is structured based on substrate types, its core focus lies in the mechanism‐driven exploration of catalytic systems. These catalytic systems exhibit versatility in facilitating the hydrogenation and hydro‐functionalization of various types of double bonds through the utilization of tridentate ligands. In this review, we present literature report of cobalt‐catalyzed hydro‐functionalization reactions. The selection of cobalt stems from its beneficial II/III redox couple state, which is useful in hydride transfer reactions. These cobalt‐based catalytic systems exhibit versatility in facilitating the hydrogenation and hydro‐functionalization of various types of double bonds through the utilization of tridentate ligands.